The Relative Risk of COVID-19 in Solid Organ Transplant Recipients Over Waves of the Pandemic - Amanda J. Vinson; Alfred J. Anzalone; Makayla Schissel; Ran Dai; Gaurav Agarwal; Stephen B. Lee; Amy Olex; Roslyn B. Mannon (Transplant International, 2024)
Solid organ transplant recipients (SOTR) are at increased risk from COVID-19. Over time, the absolute risk of adverse outcomes after COVID-19 has decreased in both the non-immunosuppressed/immunocompromised (non-ISC) general population, and amongst SOTR. Using the N3C, we examined the absolute risk of mortality, major adverse renal or cardiac events, and hospitalization after COVID-19 diagnosis amongst non-ISC and SOTR populations over five waves of the pandemic (Wave 1: Ancestral COVID; Wave 2: Alpha; Wave 3: Delta; Wave 4: Omicron; Wave 5: Omicron). Within each wave, we determined the relative risk of each outcome for SOTR versus the non-ISC population based on crude event rates, and then used multivariable cox proportional hazards models and logistic regression to determine the adjusted risk of each outcome based on SOT status. Throughout the pandemic, including during the Omicron wave (Wave 5), SOTR were at greater absolute risk for each outcome than non-ISC patients (p-values all <0.001). The adjusted risk of SOT status for each outcome was relatively stable over time (aHR 1.28–1.61 for mortality; aHR 1.31–1.47 for MACE; aHR 1.72–1.90 for MARCE; aHR 1.75–2.07 for AKI; and aOR 1.53–1.81 for hospitalization). Despite a reduction in the absolute risk of COVID-19 complications, the relative risk for SOTR versus the non-ISC population has not improved.